Role of methanesulfonic acid in atmospheric particle nucleation and growth - Rima Baalbaki; Jiali Shen; Mario Simon; Hannah Klebach; Samuel Ruhl; Jenna DeVivo; Mingyi Wang; Wiebke Scholz; Lubna Dada; Birte Rörup; Dominik Stolzenburg; Hanna E. Manninen; et al. (Nature, 2026)
Abstract Dimethyl sulfide (DMS; CH 3 SCH 3 ) from marine phytoplankton is a notable source of atmospheric sulfur 1 . Its oxidation products include sulfuric acid (SA; H 2 SO 4 ) and methanesulfonic acid (MSA; CH 3 SO 3 H), which has a higher yield than SA below 10 °C (ref. 2 ). Although SA is known to drive the formation of new particles 3 , which may subsequently grow and act as cloud condensation nuclei (CCN), the role of MSA remains unclear 4 . Here, in experiments performed under atmospheric conditions at the CERN CLOUD (Cosmics Leaving OUtdoor Droplets) chamber, we show that MSA nucleates together with ammonia (NH 3 ) below −10 °C, at rates comparable with SA-NH 3 . Moreover, MSA and SA nucleate synergistically below −10 °C, forming multi-acid molecular clusters with NH 3 . Even at ultralow NH 3 levels, MSA drives particle growth at or near the kinetic limit below 9 °C and above 40% relative humidity (RH). Because MSA and SA generally coexist at similar concentrations in cool marine regions, our findings indicate that nucleation rates may be accelerated up to tenfold and growth rates up to twofold compared with SA-NH3 alone. Our global model simulations indicate that MSA can enhance CCN concentrations, especially in polar regions. We propose that MSA might be an important driver of biogenic particles in cool, pristine marine regions of both the present-day and pre-industrial atmospheres and yet is unaccounted for in global climate models 5 .